2021
DOI: 10.2196/17564
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Recruitment Performance of Web-Based Respondent-Driven Sampling: Scoping Review

Abstract: Background Web-based respondent-driven sampling is a novel sampling method for the recruitment of participants for generating population estimates, studying social network characteristics, and delivering health interventions. However, the application, barriers and facilitators, and recruitment performance of web-based respondent-driven sampling have not yet been systematically investigated. Objective Our objectives were to provide an overview of published research using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…An option to motivate participants to take art in a study could be to increase the amount of the participation incentive. A review of WebRDS surveys found that studies that did not offer at least one guaranteed material incentive reached lower percentages of successfully recruiting participants and fewer waves, indicating that the amount of participation reward or another incentive is a big motivator for participants [ 16 ]. However, our results show that getting a high reward is actually the least important factor for forwarding an invitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An option to motivate participants to take art in a study could be to increase the amount of the participation incentive. A review of WebRDS surveys found that studies that did not offer at least one guaranteed material incentive reached lower percentages of successfully recruiting participants and fewer waves, indicating that the amount of participation reward or another incentive is a big motivator for participants [ 16 ]. However, our results show that getting a high reward is actually the least important factor for forwarding an invitation.…”
Section: Discussionmentioning
confidence: 99%
“…Higher monetary rewards have proven to be successful to create a sufficiently large sample in a study carried out in the United States [ 15 ], but this is very expensive and not feasible for many studies. High monetary rewards are also considered unethical and may lead to cheating behavior [ 16 ]. Another option to prevent recruitment chains from going extinct is to allow higher numbers of recruits per individual.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One major strength of this study was its design as a randomized intervention study. Worldwide, this study also had one of the largest samples successfully recruited using web-based RDS [ 31 ]. In addition, our CSEVs were systematically developed based on extensive qualitative and quantitative research among Turkish- and Moroccan-Dutch women [ 5 ].…”
Section: Discussionmentioning
confidence: 99%